A Novel and Efficient Synthetic Method of Benzo[f]chromen‐1‐ones and Phenyl‐4H‐chromen‐4‐one through Photooxidative Cyclization of 6‐[(E)‐2‐Arylvinyl]‐4H‐pyran‐4‐ones and 6‐[(1E, 3E)‐4‐Phenylbuta‐1, 3‐dien‐1‐yl]‐4H‐pyran‐4‐one. (30th January 2014) - Aït‐Baziz, Nabila; Hamdi, Safouane M.; Silva, Artur M. S.; Rachedi, Yahia; Hamdi, Maamar; Trari, Mohamed
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>